Effects of endolymphatic hydrops on acoustic energy absorbance. (31st July 2020) - Kobayashi, Masumi; Yoshida, Tadao; Sugimoto, Satofumi; Shimono, Mariko; Teranishi, Masaaki; Naganawa, Shinji; Sone, Michihiko
Abstract: Background: The presence of endolymphatic hydrops (EH) may cause hearing loss and affect the transmission of acoustic energy to the inner ear. Objectives: Acoustic energy absorbance on wideband acoustic immittance (WAI) was evaluated, focusing especially on EH in the vestibule. Material and methods: A total of 32 ears from 16 patients who underwent 3-T magnetic resonance imaging (MRI) to evaluate the presence of EH were examined, retrospectively. The degree of EH in the vestibule was classified into three grades (no, mild, and significant), and pure tone audiometry (PTA) and WAI were measured before and after a glycerol drip. Results: Ears with significant EH showed significantly higher hearing levels and air-bone gaps (ABG), and higher absorbance values on WAI at low frequencies (560–600 Hz) than ears with mild or no EH. Changes in absorbance values were observed in some ears without threshold change on PTA. Conclusions and Significance: This study showed significantly higher absorbance values of acoustic energy with significant vestibular EH at low frequencies. Considering ABGs observed in ears with significant EH, the presence of EH in the vestibule might cause an obstacle to the transmission of acoustic energy to the inner ear.